Chinese graphic design in the twentieth century - Minick, Scott, 1955-; Jiao, Ping, 1959- (New York : Thames and Hudson, 2010)
"From posters and advertisements to book covers and magazines, this volume presents a dazzling panoply of modern graphic design in China. Beginning with the basic traditions of Chinese graphics, the authors show how the writer and artist Lu Xun became the centre of cultural revival in the new China. We see Art Deco coming to China in the Shanghai Style, and the birth of a dynamic national design style, born of Russian Constructivism and China's own drive for new technology. The Socialist Realist art of Mao in turn adopted folk traditions to fuel the Revolutionary machine, while the continuing search for a new identity can be seen in the graphic images of protest from the summer of 1989"--P. [2] of cover.
Chinese traditions -- May fourth and the formative years -- The Shanghai style -- The progressive movement -- Proletarians and paper tigers -- Yan'an and the artistic ideal -- The revolutionary machine -- The turbulent years -- Open doors and beyond -- Reference guide.
"With 285 illustrations, 150 in color."
Originally published : United Kingdom : Thames & Hudson Ltd., 1990.
Includes bibliographical references and index.
boek